QSAR and QSPR based solely on surface properties? - Clark, Timothy (Journal of Molecular Graphics & Modelling, 2004)
The use of descriptors based on local properties calculated at the molecular surface for QSPR models is discussed. It is suggested that descriptors should be related to the physical theory of intermolecular interactions and the relationship between established surface-based descriptors and the fundamental types of intermolecular interaction is discussed. Descriptors based on local properties that do not encode the chemical constitution of the molecule directly are likely to provide less local QSPR models and favor scaffold hopping. The major disadvantage for surface-based descriptors is that they are difficult to interpret in the sense of relating predictions to the chemical composition of the molecule. This disadvantage must be alleviated by suitable model-interrogation techniques. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: QSPR; QSAR; descriptors